Mathematics in Architecture - Leroux Pazmiño, Julio Romo (Revista Universidad de Guayaquil, 2008)
In academic terms, Mathematics has the category of discipline that, in our University Faculty, covers the subjects of Algebra, Trigonometry, General Geometry, Analytical Geometry, Differential Calculus, Integral Calculus, Topography and Structural Analysis; from which those parts, topics or units most closely related to professional training are taken; fulfilling its mission of “Tax Side” of other subjects that are part of the Academic Plan of the degree.